The impacts of worker and total sales of SMEs on economic growth in Central Java Province: Evidence from ARDL Bound Test - Irianto, Heru; Cahyadin, Malik; Widyamurti, Nidyah; Harini, Harini; Sarmidi, Tamat; Wei, Yong Sze (Jurnal Ekonomi & Studi Pembangunan, 2023)
This study attempts to examine the impact of workers and total sales of SMEs on economic growth in Central Java Province throughout 2009:1 – 2020:4. The ARDL Bound Test is employed. The findings reveal that worker and total sales have a positive, significant, and linear impact on economic growth in the short-run. Total sales also have a positive, significant, and linear impact on economic growth in the long-run. Conversely, there is no evidence of workers' impact on economic growth. In addition, workers and total sales have a long-run cointegration on economic growth. Therefore, the local government of Central Java Province should emphasize the contribution of SME workers and total sales to stimulate economic growth in the long-run.